Improving Cognitive Abilities through Puzzle Playing Activities at RA Khadijah Aisyah - Wijiati; Astutik, Wiji; Hariyanti, Wiji; Palupi, Wike Dwi; Astutik, Wike Norvila (MANDAILING GLOBAL EDUKASIA, 2024)
The purpose of this study was to improve cognitive abilities through puzzle playing activities in group B at RA Kahdijah Aisyah, Jakarta, 2021. The research was carried out from 1-12 November 2021 in the 2021/2022 academic year in semester I. The subjects of the study were 8 children in group B consisting of 5 boys and 3 girls. The study was carried out for 2 cycles with the following stages: implementing, doing, acting, observing and reflecting, during the activities the researcher took the theme of fruit plants and insects. The results of the study showed the following advantages: media or materials can use materials from used goods, used children's magazines. Providing stimulus in problem solving, training eye and hand coordination, introducing the concept of shape, size and color, training children's reasoning. While the weakness is the lack of attention to the level of difficulty in assembling puzzles which must be adjusted to the child's age group. From observations made by researchers at the end of cycle II, it was found that there was an increase in children's cognitive abilities in playing puzzles. This can be seen from the percentage at the beginning of the cycle experiencing an increase, in the category not yet developing from 25% to 0% there are no more children in that category, the category starting to develop experienced an increase from 62.5% changing to 25% in this category children have experienced a reduction and changed to the category developing according to expectations from 12.5% ​​to 37.5% experiencing an increase, in the category developing very well which initially there were no children in this category in cycle II there was an increase from 0% to 37.5%. The conclusion of this study is that through puzzle playing activities can improve the cognitive abilities of children in group B at RA Khadijah Aisyah.